Immunochemical reactivity of soybean β-conglycinin subunits - Petruccelli, Silvana (2005)
The immunochemical reactivity of two polyclonal sera raised against soybean purified αα' and β subunits was analysed. We show that anti-αα' serum mainly reacts with αα' subunits and β' subunit, but it does not recognize β subunit. In addition, β subunit is not able to compete with αα' subunit for anti-αα' serum recognition sites; therefore the main immunogenic region of αα' subunits is the extension region. Both anti-αα' and anti-β sera were able to recognize E. coli produced α subunit, consequently glycosylation is apparently not required for antigen-antibody interaction. Anti-β subunit serum shows strong reactivity against soybean produced β-subunit and recombinant α subunit, while it shows weak recognition of soybean purified αα' subunits. A mutant of α subunit with the N terminal β barrel region and C terminal α helices deleted, failed to be recognized by anti-β serum. For that reason although N and C terminal domains are structurally equivalent, their immunochemical reactivity is different.